Violympic toán 9

Linh nè

Cho \(\left(x+\sqrt{x^2+2013}\right)\left(y+\sqrt{y^2+2013}\right)=2013\) . Tính P = x+y

Nguyễn Việt Lâm
Trung tá -
19 tháng 6 2019 lúc 9:25

Dễ dàng nhận ra \(x-\sqrt{x^2+2013}\ne0\), nhân 2 vế với nó:

\(\Leftrightarrow-2013\left(y+\sqrt{y^2+2013}\right)=2013\left(x-\sqrt{x^2+2013}\right)\)

\(\Leftrightarrow y+\sqrt{y^2+2013}=\sqrt{x^2+2013}-x\)

Tương tự ta có \(x+\sqrt{x^2+2013}=\sqrt{y^2+2013}-y\)

Cộng vế với vế:

\(x+y+\sqrt{x^2+2013}+\sqrt{y^2+2013}=\sqrt{x^2+2013}+\sqrt{y^2+2013}-x-y\)

\(\Rightarrow2\left(x+y\right)=0\Rightarrow P=0\)

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN